The role of South African FDI in Southern Africa - Peter Draper; Sheila Kiratu; Cézanne Samuel (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
Since 1994, the pivotal year in which South Africa held its first democratic elections, its companies have engaged in a sustained outward foreign direct investment (OFDI) thrust with substantial impact on Southern Africa, in the process generating some controversy. The paper revisits those debates and updates them in light of recent data and developments concerning the evolution of institutions supportive of South African regional OFDI, notably regulations governing investment and trade respectively. We find that South African OFDI to Africa is private sector dominated, concentrated in Southern Africa albeit evincing a discernible shift to West Africa in recent years, and its impact is on the whole beneficial. However, the actions of the South African government to support the activities of their nationals in the region are schizophrenic, particularly in its use of BITs, which seem to favour an approach that provides substantial advantages to its companies at the possible expense of host-nation policy space. We recommend therefore that in its ongoing review of its model approach to BITs the South African government should remedy this ambiguity.
Keywords: 330